Mechanism of rapid accretion-erosion transition in a complex hydrodynamic environment based on refined in-situ data - Jiang, Jie; Xie, Weiming; Zhang, Naiyu; Xu, Yuan; Zhu, Chunyan; Lin, Jianliang; Guo, Leicheng; Shen, Jian; He, Qing (Frontiers in Marine Science, 2024)
Morphological changes in estuaries are typically discussed on decadal time scales, with reported changes often exceed several decimeters. In our study, we utilized refined in-situ data to investigate bed-level changes and rapid accretion-erosion transitions during tidal cycles off the Changjiang Estuary. A field study employing a high-resolution bottom tripod system was conducted, measuring various parameters such as water level, waves, velocity profiles, near-bottom suspended sediment concentration (SSC), and bed level changes over ten tidal cycles. Our findings reveal significant and intense bed level changes occurring at the scale of tidal cycles. The data suggests that downward sediment transport plays a dominant role in the overall accretion tendency throughout the study period. Additionally, our research introduces a dynamic critical bed shear stress that increases during tidal cycles, deviating from fixed values. We also present a new quadrant analysis method to elucidate the primary processes controlling near-bed sediment transport. The results highlight the importance of horizontal advective sediment transport in frequent accretion-erosion transitions at tidal-cycle timescales. This implies a frequent exchange of sediment between adjacent shoals and channels in the seaward region of the North Channel in the Changjiang Estuary, which holds significance for future navigation and construction management.